Aplikasi Tasibar (Pendaftaran Siswa Baru) Pada Sd Negeri Cikampek Selatan I-Karawang - Surtika Ayumida (Jurnal Interkom: Jurnal Publikasi Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2018)
The era of global competition in education is required to develop rapidly, actively and dynamically. We face the challenges needed fundamental changes in the world of education itself so that the human resources generated will become human resources that are able to adapt to the times. Realizing that, SD Negeri Cikampek Selatan I as primary school felt the need to implement a new computerized student enrollment system as part of the change that replaced the new student registration system (conventional), because the computerized system can accelerate and simplify the process and minimize the mistakes that there, for that the author designed the New Student Enrollment Application Program on State Elementary School Cikampek Selatan I-Karawang, so that the program is made in accordance with the needs of the new student registration system that already exist, the authors make the design of this program ranging from input documents containing the process of filling the form of prospective students, the process of entering student data, the process of entering the data Parents, the process of entering user data and output documents containing new student cards and student reports.